Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper looks at the appropriate scope and pace of fiscal adjustment in Saudi Arabia. The economy of Saudi Arabia has started to feel the impact of the fiscal adjustment. The fiscal space analysis suggests that the authorities have some space in the next few years to undertake a more gradual fiscal adjustment than set out in the IMF staff's baseline. Although faster fiscal adjustment may have advantages in terms of limiting the rundown in net assets and taking full advantage of the current pro-reform climate, it has disadvantages when it comes to the larger impact on growth and employment in the near term, which may ultimately undermine the sustainability of the reforms.